José Carlos Mariátegui And The University Reform - Melis, Antonio (1980)
In a 1927 letter to the writer Enrique Espinoza (Samuel Glusberg), who had requested biographical data, José Carlos Mariátegui wrote, among other things: "I am a self-taught person [...] In Europe I freely frequented some courses, but without ever losing my extra-university character and even my anti-academic character". This particular placement of Mariátegui, however, had not prevented, but rather helped, his early and keen interest to the problems of university reform and school in general.